2010
DOI: 10.1128/cmr.00063-09
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Treatment, and Prevention of Human T-Cell Leukemia Virus Type 1-Associated Diseases

Abstract: SUMMARYHuman T-cell leukemia virus type 1 (HTLV-1), the first human retrovirus to be discovered, is present in diverse regions of the world, where its infection is usually neglected in health care settings and by public health authorities. Since it is usually asymptomatic in the beginning of the infection and disease typically manifests later in life, silent transmission occurs, which is associated with sexual relations, breastfeeding, and blood transfusions. There are no prospects of vaccines, and screening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
321
0
30

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(370 citation statements)
references
References 102 publications
5
321
0
30
Order By: Relevance
“…La infección por HTLV en individuos asintomáticos no tiene ningún tratamiento establecido y solo algunas de las enfermedades relacionadas con el virus lo tienen (24). El hecho de ser el causante de enfermedades graves, como la leucemia o el linfoma de células T y la paraparesia espástica tropical, ubica al HTLV en la categoría de los virus contra los cuales se trata de elaborar vacunas eficaces (25).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La infección por HTLV en individuos asintomáticos no tiene ningún tratamiento establecido y solo algunas de las enfermedades relacionadas con el virus lo tienen (24). El hecho de ser el causante de enfermedades graves, como la leucemia o el linfoma de células T y la paraparesia espástica tropical, ubica al HTLV en la categoría de los virus contra los cuales se trata de elaborar vacunas eficaces (25).…”
Section: Discussionunclassified
“…Son diversas las enfermedades relacionadas con la infección por HTLV I-II, pero solo entre el 5 y el 10 % de las infecciones progresan a enfermedad (7). Entre las descritas hasta el momento figuran la leucemia o linfoma de células T, la paraparesia espástica tropical o miopatía asociada al HTLV, la uveítis, múltiples alteraciones dermatológicas, la miositis, la polimiositis, la polineuropatía, los trastornos psiquiátricos, las infecciones oportunistas, la infección por Strongyloides stercoralis y las condiciones reumatológicas autoinmunitarias (8)(9)(10).…”
unclassified
“…Besides ATL and HAM/TSP, persistent infection by HTLV-1 also leads to a broad spectrum of diseases associated with significant morbidity: uveitis, infective dermatitis, crusted scabies, inflammatory rheumatic conditions (rheumatoid arthritis and Sj€ ogren's syndrome), peripheral neuropathies and muscle inflammation (myositis) (Gonçalves et al, 2010). The mechanisms leading to any of these conditions are currently unknown.…”
Section: Identify Biomarkers To Predict Disease Progressionmentioning
confidence: 99%
“…The prognosis is poor, with less than 1 year survival for patients (Goncalves et al, 2010). However, investigators have also shown that low prevalence of HTLV-1 infection in Iranian gastric cancer patients in comparison to controls (Tahaei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%